High expression of IQGAP3 indicates poor prognosis in colorectal cancer patients. Issue 4 (December 2019) - Wu, Jian; Chen, Zhen; Cao, Huihua; Yu, Zhan; Feng, Jin; Wang, Kai; Lu, Qicheng; Wu, Yugang
Background: The oncogene IQ motif-containing GTPase activating protein 3 (IQGAP3) is ubiquitously overexpressed in several human cancers. This study was designed to explore the expression and role of IQGAP3 in colorectal cancer. Methods: We first assessed the IQGAP3 expression level in colorectal cancer. The correlation of IQGAP3 expression with the clinicopathological characteristics and prognosis was then assessed. At last, we investigated the function of IQGAP3 in colorectal cancer by knocking down its expression in colorectal cancer cell lines. Results: Consistent with the conclusions drawn from The Cancer Genome Atlas database, IQGAP3 was upregulated in colorectal cancer at the tissue level and cellular level. Based on immunohistochemistry results of the tissue microarrays, we demonstrated that higher expression of IQGAP3 was associated with higher tumor node metastasis stage ( P = 0.005), higher incidence of lymph node metastasis ( P = 0.004), and shorter overall survival ( P = 0.022). Knockdown of IQGAP3 in colorectal cancer cell lines remarkably decreased their proliferation and migration abilities. Conclusion: Our data provide evidence that IQGAP3 significantly promote malignant progression of colorectal cancer and could serve as a potential therapeutic target.